Impact of Job Insecurity on Job Performance: Mediating role of Work Engagement - Nawaz, Sadaf; Ijaz, Sohail (Annals of Human and Social Sciences, 2022)
The Pakistani financial sector is growing significantly over the past decades, due to an increase in the branches; competition between financial institutions has increased. In the era of stiff competition, the staff plays a significant role in financial sector competition. In line with this, the current study aims to find the impact of job insecurity on work engagement and job performance of employees working in the banking sector of Pakistan. For this purpose, data were collected from four hundred employees of the banking sector by using a self-administered questionnaire. Data were analyzed by using Statistical Package for the Social Sciences SPSS software. The frequency analysis, correlation, regression, t-test, ANOVA, and mediation analysis were performed on the collected data. The findings provide that job insecurity has a significant and negative impact on work engagement and job performance. Moreover, work engagement mediates the relationship between job insecurity and job performance. The study implications and limitations have also been discussed.